Novel Insights Into the Neurobiology of the Antidepressant Response From Ketamine Research: A Mini Review - Colla, Michael; Scheerer, Hanne; Weidt, Steffi; Seifritz, Erich; Kronenberg, Golo (Frontiers in Behavioral Neuroscience, 2021)
The serendipitous discovery of ketamine’s antidepressant effects represents one of the major landmarks in neuropsychopharmacological research of the last 50 years. Ketamine provides an exciting challenge to traditional concepts of antidepressant drug therapy, producing rapid antidepressant effects seemingly without targeting monoaminergic pathways in the conventional way. In consequence, the advent of ketamine has spawned a plethora of neurobiological research into its putative mechanisms. Here, we provide a brief overview of current theories of antidepressant drug action including monoaminergic signaling, disinhibition of glutamatergic neurotransmission, neurotrophic and neuroplastic effects, and how these might relate to ketamine. Given that research into ketamine has not yet yielded new therapies beyond ketamine itself, current knowledge gaps and limitations of available studies are also discussed.